Optimizing Employee Performance: The Impact of Job Characteristics and Work Discipline at PT. Pratamaeka Bigco Indonesia - Lesmana, Gilang; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of job characteristics and work discipline on employee performance at PT Pratamaeka Bigco Indonesia. The population of this study amounted to 210 while the number of samples with the slovin formula obtained 138 respondents. Data was obtained by distributing questionnaires to selected respondents. This research uses a quantitative approach verified by multiple regression analysis. The results showed that there was a significant influence both partially and simultaneously job characteristics and work discipline on employee performance. Company management needs to consider job designs that accommodate task diversity, provide clear task identities, emphasize task significance, provide autonomy and provide feedback to employees. In addition, companies also need to encourage a work culture that emphasizes adherence to applicable rules and norms and provides adequate supervision of the implementation of these rules.